Phytochemical, Antioxidant, Anti-Inflammatory, and Thrombolytic Properties of Cleisomeria lanatum (Lindl.) Lindl. ex G. Don - Minhajur Rahman; Abu Taleb Surag; Roxy Begum; Md. Shakhuat Hossain Tusher; Mohammed Kamrul Huda (Scientifica)
For the first time, Cleisomeria lanatum (family: Orchidaceae) has been investigated for its phytochemical, antioxidant, anti-inflammatory, and thrombolytic properties. All phytochemicals studied were identified in varying degrees during qualitative screening. In quantitative screening, a maximum of 106.02 ± 0.08 mg/g alkaloids (root), 179.67 ± 8.83 mg/g phenols (stem), 17.34 ± 0.88 mg/g flavonoids (stem), 73.67 ± 1.76 mg/g tannins (stem), and 180.04 ± 0.02 μg/mL proteins (root) were detected. Antioxidant, anti-inflammatory, and thrombolytic properties were investigated using a free-radical scavenging assay, heat-induced albumin denaturation assay, and blood clotting inhibition assay. The root extracts had the most effective antioxidant (IC50 = 67.98 μg/mL) and anti-inflammatory (IC50 = 60.86 μg/mL) properties, whereas the stem extracts had the most effective thrombolytic property (IC50 = 163.8 μg/mL). The bioactivities studied also had a significant positive relationship (r = 0.9; p < 0.05) with the amount of phenolics and tannins.